The Effect of Marinating Jungga Citrus (Citrus jambhiri lush) on Physical and Organoleptic Quality of Goat Meat - Napitupulu, Ardiansyah; Nurzainah Ginting; Peni Patriani (Talenta Publisher, 2025)
Goat meat is very popular in Indonesia. Goat meat is very popular in Indonesia. One method of preserving goat meat is by treating it with acid, a process known as rarit. This study aims to determine the effect of using Jungga citrus on the physical and organoleptic quality of goat meat rarity. The experimental design used in this study was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, resulting in a total of 20 experimental units: P0=0%, P1=6%, P2=12%, P3=18%. The parameters were physical quality tests, including pH and yield of goat meat, and organoleptic tests for color, aroma, taste, and texture. The results of this study indicate that marinating goat meat with Jungga citrus solution produces significantly better organoleptic results, including texture, aroma, taste, and pH. However, there were no significant differences in color and yield between treatments. The best treatment with good results was found at a dose of 18 ml of Jungga citrus (P3) with the addition of 82 ml of mineral water. This indicates that the use of Jungga citrus in marinating goat meat effectively improves organoleptic quality such as texture, aroma, and taste. However, it does not affect the color of the meat or yield, thus maintaining the color of the meat. In conclusions Jungga citrus are good for preserving goat meat into rarit.